2011
DOI: 10.1186/1741-7015-9-114
|View full text |Cite
|
Sign up to set email alerts
|

The 'help' question doesn't help when screening for major depression: external validation of the three-question screening test for primary care patients managed for physical complaints

Abstract: BackgroundMajor depression, although frequent in primary care, is commonly hidden behind multiple physical complaints that are often the first and only reason for patient consultation. Major depression can be screened by two validated questions that are easier to use in primary care than the full Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria. A third question, called the 'help' question, improves the specificity without apparently decreasing the sensitivity of this scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The sensitivity and specificity of the two question method alone were 91.3% (81.4% to 96.4%) and 65.0% (61.2% to 68.6%), respectively. Adding the “help” question improved the specificity to 88.2% (85.4% to 90.5%) but decreased the sensitivity to 59.4% (47.0% to 70.9%) 56. Although additional studies are needed to further understand the potential benefits of a “help” question as a screening approach, there is likely value in using it to enable ongoing discussions and treatment planning in the primary care setting.…”
Section: Screening For Depression In Primary Carementioning
confidence: 99%
“…The sensitivity and specificity of the two question method alone were 91.3% (81.4% to 96.4%) and 65.0% (61.2% to 68.6%), respectively. Adding the “help” question improved the specificity to 88.2% (85.4% to 90.5%) but decreased the sensitivity to 59.4% (47.0% to 70.9%) 56. Although additional studies are needed to further understand the potential benefits of a “help” question as a screening approach, there is likely value in using it to enable ongoing discussions and treatment planning in the primary care setting.…”
Section: Screening For Depression In Primary Carementioning
confidence: 99%
“…However, a more recent cohort study on their three-question tool (with the help item) had substantially lower sensitivity (59.4%), although specificity was retained (88.2%). 25 Unlike ‘desire for help’ which was added by the Auckland investigators, 24 we chose to ask about ‘lack of energy’, which is the third essential criterion in ICD-10. We asked about insomnia as the fourth question, because insomnia is highly prevalent in depression and easily elicited in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The Auckland investigators had earlier added a question on the ‘need for help’ to their two-question screening tool 24 and reported that the sensitivity of the instrument remained high at 96%, and the specificity improved to 89%. However, a more recent cohort study on their three-question tool (with the help item) had substantially lower sensitivity (59.4%), although specificity was retained (88.2%) 25 . Unlike ‘desire for help’ which was added by the Auckland investigators, 24 we chose to ask about ‘lack of energy’, which is the third essential criterion in ICD-10.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from recent studies does not support using a third 'help' question given the significant decrease in sensitivity. Lombardo et al Lombardo et al (2011) reported a rise in cases of depression being missed: from 1 out of 10 using the two item tool; to 4 out of 10 cases being missed with the use of a 'help' question. Given that other studies (Ryan et al, 2012) also reported significant drops in sensitivity, there is concern that adding a 'help' question to a two-item screening tool will lead to an unacceptable number of missed cases of depression.…”
Section: Limitationsmentioning
confidence: 94%